2009
DOI: 10.1002/anie.200805997
|View full text |Cite
|
Sign up to set email alerts
|

Photomagnetic Switching of the Complex [Nd(dmf)4(H2O)3(μ‐CN)Fe(CN)5]⋅H2O Analyzed by Single‐Crystal X‐Ray Diffraction

Abstract: X-ray vision: Single-crystal XRD experiments (see picture) reveal the excited-state structure of the photomagnetic heterobimetallic title complex. The system shows a decrease in all the iron-ligand bond lengths, suggesting that photoexcitation involves a ligand-to-metal charge transfer or a change in the superexchange coupling between the metal centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Since crystal structure was not determined for them, we investigated TG-DTA for intermolecular hydrogen bonds in crystal lattice and 57 Fe Mössbauer spectra and Fe2p 3/2 and Fe2p 1/2 XAS for coordination environment or electronic states of Fe(III) ions. The experimental results suggested that intermolecular hydrogen bonds was important for this isotope effects found in Nd(DMF) 4 (H 2 O) 3 Fe(CN) 6 •H 2 O.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Since crystal structure was not determined for them, we investigated TG-DTA for intermolecular hydrogen bonds in crystal lattice and 57 Fe Mössbauer spectra and Fe2p 3/2 and Fe2p 1/2 XAS for coordination environment or electronic states of Fe(III) ions. The experimental results suggested that intermolecular hydrogen bonds was important for this isotope effects found in Nd(DMF) 4 (H 2 O) 3 Fe(CN) 6 •H 2 O.…”
Section: Introductionmentioning
confidence: 83%
“…Previously, we found that isotope effects of temperature dependence of magnetization for Nd(DMF) 4 (H 2 O) 3 Fe(CN) 6 •H 2 O with 2 H-substituted H 2 O and DMF ligands [6]. Since crystal structure was not determined for them, we investigated TG-DTA for intermolecular hydrogen bonds in crystal lattice and 57 Fe Mössbauer spectra and Fe2p 3/2 and Fe2p 1/2 XAS for coordination environment or electronic states of Fe(III) ions.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…A detailed view of the coordination sphere of the Dy III center is reported as reference in Figure 1: Dy III coordination number is eight, and analysis of the coordination polyhedron via use of SHAPE [18] provided evidence of a geometry intermediate between square antiprismatic, bicapped trigonal prismatic and trigonal dodecahedron geometry (see Table S1). The analysis of the packing, as well as detailed X-ray investigation on isostructural systems, [19] showed the existence of a 3D network made up of Dy III -Co III dinuclear entities where the five terminal CN groups of the {Co(CN) 6 } fragment are connected through hydrogen bonds to the Lncoordinated water molecules via crystallization water molecules. The static magnetic properties revealed that this network of hydrogen bonding interaction might result in non-negligible interdimer coupling interactions [17].…”
Section: Introductionmentioning
confidence: 99%